Jaminan Kredit Pada Perjanjian Kredit Sindikasi - Susilowati Susilowati (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
Credit Guarantee in the Syndicated Bank Credit Agreement is the most important guarantee in the Syndicated Credit Agreement which is the main discussion in this Legal Writing. The method that the author uses in this legal research is normative juridical, where the documents used as guidelines in the preparation are primary legal documents and secondary legal documents. The Credit Guarantee in the Syndicated Credit Agreement that I will use is a credit guarantee with concession rights which includes toll road concession revenues, escrow accounts, and insurance claims. The Credit Guarantee is important to cover or guarantee the Creditors in the Syndicated Bank in the event of a default or bad credit or default from the Debtor. Collateral as regulated in Law number 7 of 1992 concerning Banking as amended by Law number 10 of 1998 concerning Amendments to Law number 7 of 1992 concerning Banking, guarantee is defined as "faith in faith and ability and ability of the customer or debtor to pay off the debt or return the financing as agreed. Credit guarantees (debts) as regulated in article 1131 of the Civil Code are "all objects of the debtor, both movable and immovable, both existing and those that will exist in the future, become dependents for all individual engagements". The credit guarantee that will be discussed in this legal writing is the credit guarantee in the Syndicate Credit Agreement or syndicate loan in the form of concessions. Concession is the granting of rights, permits, or land by the Government, companies, individuals, or other legal entities. The granting of concession rights is generally applied to the development of partnerships between the government and the private sector. Syndicated credit is one of the types of credit, but the difference in Syndicated Loans is related to the number of creditors. In the Syndicated Credit Agreement, the creditor is more than one creditor. The discussion of Syndicated Credit Guarantee that will be discussed in this legal writing is the Credit Guarantee in the Syndicated Credit Agreement between PT. JJP with PT. BNI Bank, PT. Bank Mandiri, PT. Bank BRI and PT. Bank BPD Central Java in terms of the construction of the Semarang Toll Road. The object of the Credit Guarantee in the Syndicated Credit Agreement in the form of Concession Rights which is not a fiduciary or mortgage must be made in the agreement related to the risks that will occur as a result of the syndicated credit agreement, especially on the guarantee so that no party is harmed from the syndicated credit agreement and development can run smoothly. In this regard, the Government should always be innovative towards legal regulations in line with development progress so that they do not become legal problems in the future.